2000
DOI: 10.1038/sj.bdj.4800777
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dental anxiety on daily living

Abstract: The impact that dental anxiety can have on people's lives is wide-ranging and dynamic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
0
25

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 20 publications
5
110
0
25
Order By: Relevance
“…In the present study when compared to males, majority of females (50%) avoid dental visits because of anxiety and fear [ Figures 1 and 2], the results of which coincided with majority of studies, which have found higher prevalence rates for dental anxiety in females than males. [15][16][17][18][19] It was also suggested by Chellappah et al [20] that dental high-speed air turbine (drill), which is an indispensable apparatus in dental treatment, is the cause of dental anxiety in young children. In the present study, 38% of children in the age group of 6-11 years and 21% of children of age group 12-15 years have reported that sounds of drill makes them uncomfortable, followed by having to wait in reception area [ Figure 3].…”
Section: Discussionmentioning
confidence: 93%
“…In the present study when compared to males, majority of females (50%) avoid dental visits because of anxiety and fear [ Figures 1 and 2], the results of which coincided with majority of studies, which have found higher prevalence rates for dental anxiety in females than males. [15][16][17][18][19] It was also suggested by Chellappah et al [20] that dental high-speed air turbine (drill), which is an indispensable apparatus in dental treatment, is the cause of dental anxiety in young children. In the present study, 38% of children in the age group of 6-11 years and 21% of children of age group 12-15 years have reported that sounds of drill makes them uncomfortable, followed by having to wait in reception area [ Figure 3].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, there have been numerous studies that have reported high dental anxiety levels in approximately 10-20% of their participants (Locker, Liddell, Dempster, & Shapiro, 1999;Humphris, Dyer, & Robinson, 2009;Sohn & Ismail, 2005). Dentally anxious individuals frequently experience negative thoughts, feelings and fears, the fright response, sleep disturbances, and impaired social functioning in work and personal life (Cohen, Fiske, & Newton, 2000). Such individuals often avoid dental treatment and suffer detrimental effects to their oral health (Berggren & Meynert, 1984;Richard & Lauterbach, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…[5] Helping patients overcome fear and anxiety may increase regular and scheduled dental visits[6] and may ultimately improve the quality of life. [78]…”
Section: Introductionmentioning
confidence: 99%